DEFERASIROX: OVER A DECADE OF EXPERIENCE IN THALASSEMIA - Ali Taher (Mediterranean Journal of Hematology and Infectious Diseases)
Thalassemia incorporates a broad clinical spectrum characterized by decreased or absent production of normal hemoglobin leading to decreased red blood cell survival and ineffective erythropoiesis. Chronic iron overload remains an inevitable complication resulting from regular blood transfusions (transfusion-dependent) and/or increased iron absorption (mainly non-transfusion-dependent thalassemia), requiring adequate treatment to prevent the significant associated morbidity and mortality. Iron chelation therapy has become a cornerstone in the management of thalassemia patients, leading to improvements in their outcome and quality of life. Deferasirox, an oral iron chelating agent is approved for use in transfusion dependent and non-transfusion-dependent thalassemia and has shown excellent efficacy in this setting. We herein present an updated review of the role of deferasirox in thalassemia, exploring over a decade of experience, which has documented its effectiveness and convenience; in addition to its manageable safety profile.